Memantine can improve chronic ethanol exposure-induced spatial memory impairment in male C57BL/6 mice by reducing hippocampal apoptosis. (1st August 2018) - Wang, Xiaolong; Yu, Hao; You, Jiabin; Wang, Changliang; Feng, Chunmei; Liu, Zhaodi; Li, Ya; Wei, Rucheng; Xu, Siqi; Zhao, Rui; Wu, Xu; Zhang, Guohua
Highlights: Memantine improves ethanol-induced spatial memory impairment in mice. Memantine reduces ethanol-induced hippocampal apoptosis in mice. Chronic ethanol exposure increases NR1, IP3R1 and SERCA1 in hippocampus of mice. Abstract: Chronic ethanol intake can induce neuronal apoptosis, leading to dementia. We investigated the protective effects of memantine on spatial memory impairment induced by chronic ethanol exposure in mice. Male C57BL/6 mice were administered 10% (m/V) or 20% (m/V) ethanol as the only choice of drinking water. Mice were treated for 60 d, 90 d, or 180 d. Mice were treated with memantine for the same duration (daily 10 mg/kg oral). The Morris water maze and radial arm maze test were used to measure spatial memory. Mice were sacrificed after the behavioral tests. Brains were removed to prepare for paraffin sections, and hippocampi were isolated for protein and RNA extraction. 4′, 6-diamidino-2-phenylindole (DAPI) staining and immunohistochemical staining of cleaved caspase-3 were performed. Western blot analysis was used to detect the expression of cleaved caspase-3 and calcium-related proteins, including N-methyl-d -aspartic acid receptor 1 (NR1), 1, 4, 5-trisphosphate receptor 1 (IP3R1), and sarco/endoplasmic reticulum calcium adenosine triphosphatase 1 (SERCA1). The changes of NR1, IP3R1 and SERCA1 mRNA were detected using quantitative polymerase chain reaction (qPCR). The results revealed that chronic ethanol exposure induced spatial memory impairment in mice, as well as increasing the expression of NR1, IP3R1 and SERCA1, the activation of caspase-3 and apoptosis in hippocampus. The effect was particularly prominent in the 20% ethanol group after 180 d exposure. Memantine decreased ethanol-induced spatial memory impairment, caspase-3 activation and apoptosis in the mouse hippocampus. These results suggest that disruption of intracellular calcium balance by ethanol can induce caspase-3 activation and apoptosis, which underlies subsequent spatial memory impairment in mice.